Pengaruh Keragaman Produk Dan Kepercayaan Terhadap Minat Beli Online Saat Pandemi Covid-19 - Tiara Cantika Putri; Ce Gunawan (CV ODIS, 2021)
This study was conducted to examine the extent of the influence of product diversity and trust in online buying interest during the Covid-19 pandemic in the millennial community in Sukabumi. This type of research is categorized as a descriptive study using a quantitative approach. The population is all millennials in Sukabumi. In this study, the number of samples used 100 respondents. Data collection techniques through online questionnaires using a Likert scale. Data sources are primary data and secondary data. Testing the quality of the instrument using the validity test and reliability test. The next test is testing the fulfillment of classical assumptions and multiple linear regression analysis, including t statistical testing and F statistics. The results of the study found that partially and simultaneously product diversity and trust variables have a positive and significant effect on purchase interest variables.